Critical Factors for Selecting a Neutral to Support Alternative Dispute Resolution Methods in the Construction Industry - Abdollah Saeb; Othman Bin Mohamed; Mohd Suhaimi Bin Mohd Danuri; Norhanim Binti Zakaria (Salehan Institute of Higher Education, 2018)
Alternative dispute resolution methods (ADR) were developed in the construction industry to acquire suitable solutions. These methods are classified based on the role of the third party (neutral). Third-parties can play multiple roles in the ADR process including a facilitative, advisory, determinative or combined. The authorities of the third-party in the types of ADR techniques are different. Despite the importance of a third party in the ADR process, previous studies are not clearly identified factors for selecting them. The purpose of this research is to provide critical factors for neutral to support ADR methods in the construction industry. This research also, highlights the role of neutral in common ADR techniques. Random sampling was used for quantitative data collection. Of the 200 experts invited to fill in the questionnaire, 112 experts participated. To provide critical factors the factor analysis was used. The research found four critical factors for selecting supporting ADR neutrals in construction including; familiarity with legal and technical issues, being accepted by parties, efficiency and fairness. It can be concluded that selecting neutral party using the critical factors is efficient because the selection of a third-party in ADR is based on many variables is very difficult.